Nationwide efforts for trauma-informed care implementation and workforce development in healthcare and related fields: a systematic review - Oral, Resmiye; Coohey, Carol; Zarei, Kasra; Conrad, Aislinn; Nielsen, Anne; Wibbenmeyer, Lucy; Segal, Rachel; Wojciak, Armeda Stevenson; Jennissen, Charles; Peek-Asa, Corinne (The Turkish Journal of Pediatrics, 2020)
There is building evidence that Adverse Childhood Experiences without early and proper intervention leads to subsequent short- and long-term behavioral, social, physical and mental health problems. Practitioners, researchers, and healthcare systems have been implementing trauma-informed care (TIC) in a variety of health and human services settings, resulting in improvements in clinical care and prevention of illness by identifying high risk populations. This has led to positive health outcomes including improved compliance, better access to mental health services and reduced health care costs. A systematic review was conducted of studies that focused on TIC implementation in healthcare settings, statewide TIC implementation, impact of adverse childhood experiences on health outcomes, impact of TIC on health outcomes, and evaluation of TIC implementation. A search was conducted in March 2019 to identify studies in PubMed, Medline, and other online literature. We limited our search to articles published in English after 2000. This article aims to review the components of TIC phases of implementation in healthcare settings, success stories across the nation to help the readers understand the importance of a paradigm shift to improve healthcare delivery and health outcomes and to prevent illness starting from childhood with a family centered care perspective.